Random coding method for coherent detection φ-OTDR without optical amplifier - Li, Peihong; Wang, Yu; Yin, Kang; Liu, Xin; Bai, Qing; Zhang, Hongjuan; Gao, Yan; Jin, Baoquan (Optics and lasers in engineering, 2023)
•Random coding method can bring SNR enhancement without loss of the sensing bandwidth.•The sensing distance can be extended without any light amplification.•System hardware is optimized and the cost is reduced. In this article, a coherent detection phase-sensitive optical time-domain reflectometry (φ-OTDR) without optical amplifier using random coding method is proposed. A series of pulses modulated by random codes are injected into the optical fiber to enhance the signal-to-noise ratio (SNR) and extend the sensing distance. The code only needs one sequence for decoding, which maintains the original sensing bandwidth. Simultaneously, the coding probe pulse does not pass through any optical amplifier to avoid the transient effect. Experimental results show that the SNR of the demodulated signal is improved 14.19 dB by using 128-bit random coding pulse. In the traditional single pulse scheme with erbium doped fiber amplifier (EDFA), the intensity SNR at 25.521 km is only 5.39 dB with a 40 ns pulse width, and the vibration signal cannot be effectively demodulated. In the proposed system with the same pulse width, the external disturbance can be located successfully at 42.338 km, and the SNR of the demodulated signal is 21.5 dB.